Evaluasi Implementasi Kurikulum Merdeka di MAN Kapuas Kabupaten Kapuas: Evaluation of the Implementation of the Merdeka Curriculum at MAN Kapuas, Kapuas Regency - Supriadi, Gito; Azis, Abdul; Iskandar, Ali; Nuha, Ulin (Anterior Jurnal, 2025)
The study was inspired by the Directorate General Decree of Islamic Education, Ministry of Religion of Indonesia Number 1443 of 2023 about the school implementers of the ‘Merdeka’ Curriculum for the 2023/2024 academic year, one of which is Madrasah Aliyah Negeri (MAN) Kapuas appointed as the curriculum implementer. It is, therefore, an evaluation is needed to be carried out. The study was aimed at (1) describing the suitability of planning with the process standard; (2) describing the suitability of implementation with the process standard; and (3) describing the suitability of assessment with the assessment standard. The study employed a qualitative method using evaluation research. The gap model was employed in the study. Interviews, observation, and documentation were used to collect data. The analysis revealed that (1) the planning carried out at MAN Kapuas Regency is suitable with the standard process That is, the planning covered learning objectives, steps for learning activities, and assessments, (2) the implementation of learning at MAN Kapuas Regency has been carried out based on the process standard. It was carried out in an interactive, inspiring, fun, challenging atmosphere, motivating students to participate actively, and has also implemented individual learning; (3) the assessments at MAN Kapuas are based on assessment standards. It was at the beginning, during, and after the learning process. However, have not been able to carry out the assessment optimally in the P5 activity (Strengthening Pancasila Student Profile Project).